2001
DOI: 10.1038/sj.bmt.1703286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transplantation regimen on prognostic significance of high-level minimal residual disease before allogeneic stem cell transplantation in children with ALL

Abstract: Summary:High MRD levels before transplantation in children receiving T cell-depleted unrelated grafts for relapsed ALL were associated with a 100% relapse risk. We report on two children with relapsed ALL who underwent non T cell-depleted BMT from unrelated donors. Despite a high residual tumor load pretransplant and the occurrence of only aGVHD grade I, they are still in second complete remission 2.7 and 5.2 years after transplantation, respectively. Thus, we propose that the transplant regimens influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Minimal residual disease levels prior to HSCT are directly related to risk of relapse post‐HSCT, particularly in ALL (Krejci et al , ; Bader et al , ; Leung et al , ). It should be noted, however, that high levels of MRD pre‐transplant do not completely preclude success (Schneider et al , ; Bader et al , ; Leung et al , ). Moreover, we found that the adverse prognostic impact of any given level of MRD was lower in children with ALL or AML transplanted in recent years (2000–2007) as compared to earlier cohorts (Leung et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Minimal residual disease levels prior to HSCT are directly related to risk of relapse post‐HSCT, particularly in ALL (Krejci et al , ; Bader et al , ; Leung et al , ). It should be noted, however, that high levels of MRD pre‐transplant do not completely preclude success (Schneider et al , ; Bader et al , ; Leung et al , ). Moreover, we found that the adverse prognostic impact of any given level of MRD was lower in children with ALL or AML transplanted in recent years (2000–2007) as compared to earlier cohorts (Leung et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…El número de copias del gen CBFb-MYH11, tras la inducción y consolidación, fueron significativamente más altas en los que recayeron comparado con los que mantuvieron remisión completa, lo que confiere a esta determinación de EMR un importante valor predictivo 22,23 . El éxito de los trasplantes de progenitores hematopoyéticos (TPH) en leucemias infantiles, tanto alogéni-cos como autólogos, depende de la persistencia o reaparición de EMR en el paciente trasplantado [31][32][33][34] . Estudios retrospectivos muestran que la presencia de EMR en LAL, analizada previamente a un TPH, se asocia a un alto riesgo de recaída posterior 31 .…”
Section: ¿En Qué Momento Es úTil Realizar La Determinación De Emr?unclassified